Tempo de quê?: as percepções das crianças sobre o tempo escolar na transição da educação infantil para os anos iniciais - Santos, Fernando Ferrão dos (2016)
This research was linked to the Master's degree in Education, the Program of Graduate Studies in Education of the Federal University of Santa Maria, in the line of School Practices and Public Policies (LP2) and the Group for Research and Contemporary Studies in Education and Childhood - GIECEI. The study aimed to investigate the children's perceptions of school, a pre-school class in the city of Julio de Castilhos / RS, amid the transition from kindergarten to elementary school. The investigative journey took aspects of qualitative ethnographic research, based on studies of Minayo (1996), André (2005) and Bakhtin (2006). As an investigative methodology was used participant observation, based on Lapassade (2001), and as data collection instruments logbook and pedagogical documentation through drawings produced by children (Francischini and Fields, 2008). Analysis of the data produced during the survey was conducted from the content analysis, which for Bardin (2009) is understood as a set of analytical techniques of communication that uses systematic procedures and description of the content of the messages goals. With this study, we show the actions of children in the process of creating meanings, an insertion movement in the school context and compliance with the own demands and curiosities, in the midst of organizing time, which was understood as a cognitive category socially constructed that encompasses both individual subjectivity as a set of cultural and social meanings (Bondioli, 2004). This was possible partly because the theoretical approach adopted in this research, based on the pedagogical documentation, which was used the logbook in view of the daily lesson of Zabalza researcher (1994), and the drawings of children taking into account the theoretical contributions of Oliveira-Formosinho and Azevedo (2002), which were fundamental in the analysis of data built up over the work. There are many challenges that education must face and one of them is to get the child to be recognized as a subject of rights, citizen. And as the results arrived at, the research shows that it is necessary to ensure the child conditions for its development, not only in the letter of the law, but concrete and real plane in which the right to play is legitimately recognized, as well as your time and your space are respected and also gain its due importance.